Evaluation of Skills for Success-Reading and Writing Based on Criteria Designed by Alan Cunningsworth - Saud, Wafa Ismail (Technium Social Sciences Journal, 2023)
This study aimed to evaluate the textbook “Skills for Success- Reading and Writing” based on the criteria of a good textbook by Cunningsworth (1984). This book is taught for level 1 at King Khalid University. A qualitative method with content analysis was used for collecting and analyzing the data. Cunningsworth (1984)’s criteria involve eight categories, language and content, selection and grading of language items, presentation and practice of new language items, language skills and communicative abilities, supporting materials, motivation, overall evaluation and adaptation and innovation. The findings revealed that the textbook meets all criteria of a good textbook by Cunningsworth. However, the author can make some improvements, such as developing more productive tasks, teaching the most frequent grammatical patterns, and finally, developing pronunciation and spelling tasks.